2018
DOI: 10.3390/ma11101879
|View full text |Cite
|
Sign up to set email alerts
|

Fabricating a Novel Intragranular Microstructure for Al2O3/GdAlO3 Ceramic Composites

Abstract: In order to make the embryonic form of intragranular structure, the Al2O3/GdAlO3 system was selected due to its excellent mechanical properties. Gd2O3 and Al(NO3)3·9H2O were used as the starting materials. A co-precipitation method was used for the preparation of fine ceramics and applied to synthesize the nano-powder of GdAlO3 firstly. Then, the nano-powder of GdAlO3 was mixed with the precipitates by the second co-precipitation method. After drying and calcination, the compound powder with eutectic compositi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…A first step to overcome these drawbacks consists in the use of sintering aids [16,17], whereas a more effective way to do it relies on the preparation of very reactive powders which are capable to be sintered at significantly reduced temperatures. Many synthesis routes fulfill this requirement and, among them, the most common ones are the hydrothermal treatment [18,19], the sol–gel route [20] and the coprecipitation method from aqueous solutions [4,21]. Moreover, among those processes, the coprecipitation method is the simplest and cheapest one, even if powders prepared via coprecipitation from aqueous solutions are often characterized by high degrees of agglomeration causing the formation of hard aggregates during the calcination and sintering steps, thus consequently impairing severely the final density of the electrolyte [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…A first step to overcome these drawbacks consists in the use of sintering aids [16,17], whereas a more effective way to do it relies on the preparation of very reactive powders which are capable to be sintered at significantly reduced temperatures. Many synthesis routes fulfill this requirement and, among them, the most common ones are the hydrothermal treatment [18,19], the sol–gel route [20] and the coprecipitation method from aqueous solutions [4,21]. Moreover, among those processes, the coprecipitation method is the simplest and cheapest one, even if powders prepared via coprecipitation from aqueous solutions are often characterized by high degrees of agglomeration causing the formation of hard aggregates during the calcination and sintering steps, thus consequently impairing severely the final density of the electrolyte [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the efforts of the world scientific community to solve the global problem of processing non-conductive ceramics and nanoceramics due to the inclusion of the secondary phase, the issue remains unresolved [34,37,47,48,50,51,88,102]. The main issue that hampers the advances is related to the material of the secondary phase, which often is not widely available for use in the conditions of real production [33,34,36,37,40,44,89,103]. Besides, the material of the secondary phase can significantly change the appearance of ceramics, such as transparency and color, which directly affects and restricts the areas of its potential application [7,8,39,104].…”
Section: Discussionmentioning
confidence: 99%
“…-The creation of a new class of nanocomposite ceramics with the inclusion of the conductive phase allowing the machining of blanks in order to obtain the finished product with the use of minimal technological effort and the absence of direct contact between the material and tool, i.e., using the electric discharging methods of machining [33][34][35][36][37][38][39]; -…”
Section: Scientific Problemmentioning
confidence: 99%
“…Al-based MMCs have been widely used in the aircraft, military, aerospace, and automotive industries [6,7]. Owing to the low density, low melting point, high specific strength and thermal conductivity of Al, a wide variety of reinforcement particles, including ceramic particles (SiC, Al 2 O 3 ), metal particles (Cu, Mg) and graphite, have been used to reinforce it in order to further improve its mechanical and physical properties [8,9,10,11,12,13]. Kollo et al [14] reported that the ultimate tensile strength of the Al-based MMCs could increase from 205 MPa to 420 MPa with an increase in the volume fraction of SiC nanoparticles from 1 to 10%.…”
Section: Introductionmentioning
confidence: 99%